"Go Home, Purūravas": Heterodox Rhetoric of a Late Rigvedic Dialogue Hymn. Issue 2 (4th May 2019) - Thornton, Elizabeth
ABSTRACT: This essay attempts to de-link the study of the Rigveda from both colonial philology and ongoing Hindu nationalist projects. It brings the rhetoric of form, especially as theorized by Kenneth Burke, to open up space for critics and commentators with a broader range of relationships to Brahmanical liturgy. To further the goal of delinking, it first narrows the scope of analysis to dialogue hymns, which are reminiscent of debates found within Buddhist conversion narratives rendered in versified Sanskrit. It then centers formal linguistic figures that these two layers of Sanskrit poetry have in common. Finally, conceptualizing these formal devices, it uses analytic categories from a South Asian critical tradition ( alaṃkāraśāstra ). Framed and constrained in this manner and applied to the (ex-)lovers' quarrel of Purūravas and Urvaśī (in R.V. 10.95), a Burkean analysis reveals an exchange that both satisfies the "appetites" and allays the concerns of conservative audiences, who otherwise might fear that their wives could follow Urvaśī's example and happily part with their wedded partners-in-sacrifice.